FACTORS AFFECTING RESEARCHERS PERFORMANCE IN THE INDONESIAN INSTITUTE OF SCIENCES - Wasfi, Sabrul; Mulyati, Heti; Purwono, Joko (Jurnal Aplikasi Manajemen, 2020)
The Performance of Indonesian researchers is relatively low at the international and ASEAN levels. Moreover, LIPI (Indonesian Institute of Sciences) as one of the largest research institutions in Indonesia, its ranks on webometrics continue to decline. This study aims to prove the factors that influence the performance of LIPI researchers.Â  This study aims to examine the effect of competence, training, organizational support, organizational climate, and researchers'characteristics on performance. With a stratified proportional sampling data collection technique, we obtained 153 researchers in research centers in LIPI. Data was collected using a questionnaire manually and online. Data were analyzed using partial least square (SEM- PLS), multiple linear regression, and descriptive statistics. The analysis concluded that research competence, training, functional position, academic qualification, and age had a significant effect on performance. But, organizational support and organizational climate had no significant effect on performance. Research competence contributes to the highest influence on performance. From this study, we recommended an increasing frequency of organizing international scientific writing training to improve researcher performance.